A life in crystallography. Issue 13 (10th March 2020) - Colón, Jorge L.; Martí, Angel; Sun, Luyi
Abstract : This themed issue honors Professor Abraham Clearfield FRSC who has been a luminary for more than 60 years in the fields of crystallography, inorganic solid-state chemistry and materials science, and has touched the lives of many colleagues and friends during this time.